Classification of Impact Damage on A Rubber-Textile Conveyor Belt: A Review - Alviari, Luana Putri; Anggamawarti, Merlina Fitri; Sanjiwani, Yudistira; Risonarta, Victor Yuardi (International Journal of Mechanical Engineering Technologies and Applications, 2020)
A conveyor belt is one type of goods transportation in technological processes, particularly in the mining industry. The belt is the important material and principal part of the conveyor belt. The overall quality of the conveyor belt as its service life and impact loads are very important factors. Therefore, the purpose of this paper is to classify the types of impact damage that may occur in rubber-textile conveyor belts. In many works, many types of conveyor belts are tested at various levels and the type of impacting material. The level of damage occurred is investigated by using probability theory. Particularly, the evaluation of experimental test data and predictive modeling is carried out using the NaÃ¯ve Bayes classification.